(untitled) (International Journal of Engineering and Computer Science, 2025)
In recent years, the integration of machine learning (ML) models into cybersecurity frameworks has revolutionized the detection and mitigation of sophisticated cyber threats. However, this technological advancement has concurrently introduced new vectors of vulnerability, particularly through adversarial machine learning (AML) techniques. One of the most insidious forms of AML is the poisoning attack, which compromises the training phase of ML algorithms by injecting carefully crafted, malicious data points to subtly distort model behavior, thereby undermining the reliability of cybersecurity applications. This research paper provides a comprehensive investigation into contemporary defense mechanisms designed to counteract poisoning attacks within cybersecurity-centric machine learning systems. The study systematically reviews existing academic literature, categorizing and evaluating a range of defensive strategies including data sanitization, adversarial training, differential privacy, ensemble learning, federated learning, and anomaly detection. A comparative framework was employed to assess these mechanisms based on three critical criteria: defense effectiveness, computational cost, and practical applicability in real-world cybersecurity settings. Quantitative insights were derived from synthesized case studies and previously published experimental results, focusing on metrics such as model accuracy, true positive rates, and false positive rates under both normal and adversarial conditions. Notably, the findings highlight that while adversarial training and federated learning demonstrate superior resilience against poisoning attacks, they impose higher computational overheads compared to more lightweight methods like data sanitization and anomaly detection. Differential privacy, though effective in preserving data confidentiality, occasionally degrades model accuracy. To enhance the depth of analysis, graphical visualizations were included to illustrate the trade-offs between defense effectiveness and computational cost, alongside the observable impact of poisoning attacks on model performance metrics. The research also identifies significant gaps in current methodologies, advocating for future exploration in hybrid defense systems, explainable AI (XAI)-enhanced adversarial detection, and blockchain-integrated ML pipelines to ensure data integrity and auditability. This paper underscores the urgent necessity for scalable, context-aware, and transparent defense mechanisms in the evolving field of adversarial cybersecurity. The proposed comparative framework and analytical insights aim to inform researchers, security architects, and AI developers in fortifying machine learning models against increasingly sophisticated poisoning attacks.